Jumping off Arnstein's ladder: social learning as a new policy paradig m for climate change adaptation - Collins, Kevin; Ison, Ray (Environmental Policy and Governance, 2009)
Participation of citizens, groups, organizations and businesses is now an essential element to tackle climate change effectively at internat ional, European Union, national and local levels. However, beyond the general imperative to participate, major policy bodies offer little gu idance on what this entails. We suggest that the dominance of Arnstein 's ladder of citizen participation in policy discourses constrains the ways we think about, and critically the purposes we ascribe to, parti cipation in a climate change context. We suggest an alternative framin g of climate change, where no single group has clear access to underst anding the issue and its resolution. Thus adaptation is fundamentally dependent on new forms of learning. Drawing on experiences of social l earning approaches to natural resource managing, we explore how a comm itment to social learning more accurately embodies the new kinds of ro le, relationship, practice and sense of purpose required to progress a daptive climate change agendas and practices. Copyright © 2009 John Wi ley & Sons, Ltd and ERP Environment.
Keywords: Arnstein's ladder; Climate change; Co-evolutionary adaptation; Natural resource management; Participation; Social learning